Natalizumab, rituximab and fingolimod as escalation therapy in multiple sclerosis. (12th March 2019) - Boremalm, M.; Juto, A.; Axelsson, M.; Novakova, L.; Frisell, T.; Svenningsson, A.; Lycke, J.; Piehl, F.; Salzer, J.
Abstract : Background and purpose: Breakthrough disease on first‐line injectables in relapsing‐remitting multiple sclerosis (RRMS) is a common clinical situation where comparative studies between different escalation therapies are lacking. The aim of this study was to compare the efficacy, safety and medication persistence of natalizumab (NTZ), rituximab (RTX) and fingolimod (FGL) as escalation therapy in RRMS. Methods: Patients switching from interferon or glatiramer acetate to NTZ, RTX or FGL due to breakthrough disease were identified through the Swedish multiple sclerosis (MS) registry at four large MS centers in this retrospective observational study. Data were collected from the MS registry and medical charts. Hazard ratios (HRs) for relapses, adverse events and drug discontinuation with 95% confidence interval (CI) were calculated using multivariable confounder‐adjusted Cox proportional hazard models. Results: A total of 241 patients were included. The annualized relapse rates were 0.02 for NTZ, 0.03 for RTX and 0.07 for FGL. Compared with NTZ, the adjusted HR for relapse was 1.0 (95% CI, 0.2–5.6) for RTX and 3.4 (95% CI, 1.3–9.2) for FGL. The annualized drug discontinuation rates were 0.15, 0.01 and 0.15 for NTZ, RTX and FGL, respectively. The adjusted HR for drug discontinuation was 0.05 (95% CI, 0.01–0.38) for RTX and 1.0 (95% CI, 0.6–1.7) for FGL vs. NTZ. Conclusions: In patients with RRMS on interferon/glatiramer acetate with breakthrough disease, switching to NTZ or RTX was associated with less disease activity compared with FGL. RTX displayed superior medication persistence compared with both NTZ and FGL.